EFFECTIVENESS OF BACILLUS SPP. PRESS ON BLUE GREEN ALGAE (BGA) CAUSING OFF-FLAVOR IN CATFISH CULTIVATION - Djamil, Moh. Zharfan Abd.; Rukmono, Djumbuh; Utari, Heny Budi (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2020)
A problem that often occurred for the actor of catfish cultivation was an indication of smelly mud/dirt/muddy taste (off-flavors). Off-flavors were identified from chemical geosmin compound (GSM) and 2-Methyl Iso-borneol (MIB) produced by Cyanophyceae (Blue Green Algae or BGA) and actinomycetes. This soil odor compounds was soluble in water, into the body of fish through the gill and forwarded to the fatty tissue of fish, so that the fish meat was finally mud-smelly/dirt/musty. Probiotics was an attempt to reduce the compounds that caused off-flavors. The use of probiotics containing Bacillus spp. on feed could degrade organic matter through bioremediation digestive organs and environmental fish farming to minimize the accumulation of organic matter. The reduced of organic matter in waters on total organic odor, has impacted on the percentage of BGA as cause of mud-smelly in waters, especially for species Oscillatoria Sp. In this study, the researchers used Bacillus spp. to treat 10 ml/kg and 20 ml/kg of feed that can indirectly lower the percentage of BGA, Oscillatoria population Sp. and off-flavor in catfish meat as compared to controls.